Irrigation simulation model for various crops in Selangor State, Malaysia - Roy, Swapan Kumar; Ahmad, Desa (Universiti Putra Malaysia, 1999)
An irrigation simulation model has been applied to determine the daily water requirement and irrigation interval for the off-season. In this model, the reference crop evapo-transpiration is estimated by Blaney-Criddle method. The model determines the gross amount of daily water requirement for a selected cropping pattern consisting of crops such as rice, sweet corn, potato, tomato, and cauliflower for the off-season (April to August) for the climatic condition of Selangor State of Malaysia. The irrigation interval for rice varies from 6 to 30 days and average application is 60 mm depth of water whereas potato and tomato require irrigation during flowering stage. Sweet corn and cauliflower need no irrigation due to available rainfall throughout the season. A computer program of the simulation model is written in QBASIC.